Peran Audit Internal dalam mencegah fraud di tengah wabah covid-19 (Study Empiris RSUD Dr. Soetomo Surabaya) - Syarifah hatijah; Indrawati Yuhertiana (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2021)
This study describes the role of internal auditors in preventing fraud against budget execution in the midst of the covid-19 pandemic. This study aims to obtain empirical evidence regarding the role of the internal supervisory unit as an internal audit in hospitals in preventing fraud in the midst of the covid-19 outbreak (A Study at Dr. Soetomo Hospital Surabaya)